GaN-based Power amplifiers for microwave applications - Moreno-Rubio, Jorge Julián; Angarita-Malver, Edison Ferney; Restrepo-Burgos, Norma; Rodríguez, Julián Leonardo; Salamanca, Juan Mauricio; Cuevas-Carrero, William Alexander (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents a discussion about the design strategies of different kind of power amplifiers for RF/Microwave appli- cations, such as the tuned load power amplifier, class F, class F-1 and Doherty. Furthermore, it is shown the continuous wave characterization of the amplifiers above mentioned. A comparison between the obtained results, in terms of gain, efficiency and output power is presented.